COMPARATIVE ANALYSIS OF BAITUL MAAL WAT TAMWIL EFFICIENCY IN INKOPSYAH BMT MEMBERS IN JAVA ISLAND WITH SUMATRA ISLAND 2013-2017 PERIOD - Alief Fathomy Rahman; Lina Nugraha Rani (Ekonomi Islam, 2021)
This study aims to analyze the comparison of the efficiency of Baitul Maal wat Tamwil on BMT members of Inkopsyah in Java and Sumatra Island in 2013-2017. This research is quantitative research with a descriptive approach. To test the hypotheses of the samples, we use Data Envelopment Analysis (DEA) method. Assuming Constant Variables to Scale (CRS), Baitul Maal wat Tamwil obtained an average efficiency score over the study period of 0.88799544. However, using the VRS assumption, Baitul Maal wat Tamwil achieved a better average efficiency score with a score of 0.93110024. The results of this study are expected to be useful for stakeholders relating to the sustainability of BMT, such as for implementers or practitioners in the related BMT, for academics or researchers interested in the same topic, and for the community as customers of BMT itself. Keyword: BMT, Inkopsyah, efficiency, CRS, VRS.